Precipitation of Polypropylene and Polyethylene Terephthalate Powders Using Green Solvents via Temperature and Antisolvent-Induced Phase Separation - Benedikt Hanschmann (Advances in Polymer Technology)
Polymer dissolution and precipitation are two common processes for the production of polymer powders, especially for cases where usual means of comminution are not applicable. I investigated six dissolution–precipitation processes based on high-boiling sustainable green organic solvents and antisolvents for the polypropylene and polyethylene terephthalate with respect to apparent particle morphology for a closed loop production scheme. Of the investigated processes two are considered antisolvent-induced precipitations whereas the other four can be considered temperature induced. The applied solvents included p-cymene, dibutoxymethane, ethylbenzoate, γ-valerolactone, ethanol, and hexanol. All processes yielded powders consisting of agglomerated primary particles at a powder dry substance of less than 25% by weight. The produced powders consist in all cases of agglomerates of smaller primary particles.